The Correlation Between Body Mass Index And Acne Vulgaris - Raditra, Ghinia Zati Hulwani; Sari, Mutiara Indah (Sumatera Medical Journal, 2020)
Skin diseases for teenagers and young adults are acne vulgaris. It occurs through various factors, such as food and obesity. Foods with a high glycemic index (IG) are associated with a high incidence of acne vulgaris. By considering the Body Mass Index, the glycemic load has a significant relationship with the occurrence of acne vulgaris. The relationship between BMI and acne vulgaris in the class of 2016 FK USU student population. This study was analytic design with cross sectional design, a sample by 2016 FK USU students. Data collected by conducting a physical examination, measurement of height, weight, determination of BMI, and nutrient intake using the Food Frequency Questioner (FFQ) questionnaire. Data is collected using SPSS program. Then, a Chi-Square test was performed. The incidence of acne vulgaris in students 2016 FK USU was 46.1%. With majority of locations arising acne vulgaris is in the face of 35.6%. The most common age suffering from acne vulgaris is 21 years (22.2%). Women (30.6%) from acne vulgaris than men (15.6%). The most BMI in the sample is underweight to normal body weight (31.7%). The results of data analysis, found no relationship between BMI and acne vulgaris p = 0.336